In‐vivo evaluation of corneal collagen fibrils pattern to detect Keratoconus - Ancona, Chiara; Passaro, Maria Laura; Airaldi, Matteo; Lipari, Eugenio; Semeraro, Francesco; Kaye, Stephen B.; Romano, Vito (Acta ophthalmologica (Oxford, England), 2024)
Aims/Purpose: The corneal stroma, is formed by fibrous connective tissue containing collagen fibrils that are super‐organized in lamellae. In keratoconus (KC), intra‐lamellar and inter‐lamellar disrupted organization causes a progressive thinning and corneal ectasia. The LUMAXIS is a new medical device specifically designed to evaluate the effects of the interaction between polarized light and corneal stroma. It identifies the orientation of collagen fibrils in the cornea, highlighting ultrastructural changes of the tissue. The purpose of this study was to employ the LUMAXIS to discriminate changes in the pattern of corneal collagen fibrils to detect keratoconus. Methods: Patients with KC and controls were included in this prospective study. Corneal tomography (Pentacam) was acquired as well as polarimetric interferometry (LUMAXIS, Phronema S.r.l., Bari, Italy). Custom software was developed to improve the visualization of the representative cross by extracting the histogram equalized luminance to provide a numerical outcome. We then fit a set of ellipses to the image in a semi‐automatic approach, aiming to capture the boundaries of the iris, pupil, each four quadrants of the cross, and eyelids. Combining this information, we are able to obtain a cross parameter. A correlation between cross outcome and Kmax was calculated. Results: A total of sixty eyes of sixty patients were included: 30 healthy subjects (including 60 eyes, mean age of 38.0 ± 13.2 years) and 30 patients with KC (60 eyes, mean age of 39.2 ± 12.9 years). Maximum keratometry value were 59.4 ± 11.2 D in the KC group and 45.3 ± 0.8 D in the healthy group. The cross parameter was 0.41 ± 0.028 in the KC group and 0.24 ± 0.055 in the healthy group. Using only measures taken from the cross resulting from the Lumaxis scan, we were able to distinguish between KC and healthy eyes. Conclusions: The interferometric analysis of diffractive and polarizing effects related to the birefringent properties provides new morphological information at corneal fibrils level. A different corneal pattern of corneal collagen fibrils can be recognized in keratoconus patients compared to healthy patients.